Upregulated circRNA hsa_circ_0071036 promotes tumourigenesis of pancreatic cancer by sponging miR-489 and predicts unfavorable characteristics and prognosis. Issue 4 (16th February 2021) - Han, Xu; Fang, Yuan; Chen, Pingping; Xu, Yaolin; Zhou, Wentao; Rong, Yefei; Li, Jian-Ang; Chen, Wei; Lou, Wenhui
ABSTRACT: Circular RNAs (circRNAs), the new stars of endogenous non-coding RNAs, are dysregulated in various tumors including pancreatic cancer. Here, we aimed to investigate the biological functions of hsa_circ_0071036 in the tumourigenesis and progression of pancreatic ductal adenocarcinoma (PDAC) and its clinical implications. The differential expression profile of circRNAs in 4 pairs of PDAC tissues was analyzed by microarray assay. Quantitative real-time PCR and fluorescence in situ hybridization (FISH) were utilized to determine the expression patterns and their clinical significance. Functional experiments in vitro and in vivo were performed to explore whether hsa_circ_0071036 functions as an oncogenic circRNA in PDAC. Mechanistically, RT-qPCR, dual luciferase reporter and RNA pull-down assays were conducted to identify the interaction between hsa_circ_0071036 and miR-489 in PDAC. Hsa_circ_0071036 was remarkably overexpressed in PDAC cell lines and tissue samples, which negatively correlated with miR-489 expression. Aberrant expression of hsa_circ_0071036 correlated with poor clinicopathological characteristics and prognoses of PDAC patients. Knockdown of hsa_circ_0071036 suppressed proliferation and invasion and induced apoptosis in vitro . Moreover, the in vivo xenograft model confirmed that silencing of hsa_circ_0071036 attenuated tumor growth. Mechanistic analyses indicated that hsa_circ_0071036 acted as an efficient miRNA sponge for miR-489 in PDAC. In summary, our study revealed that upregulated hsa_circ_0071036 promotes PDAC pathogenesis and progression by directly sponging miR-489, which implies an important role for this circRNA-miRNA functional network.